INTERACTION OF TRADE AND FINANCIAL LINKAGES IN THE FREE TRADE ZONES - V. Shevchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Different models of free trade agreements (FTA) and free trade zones (FTZ) are considered in the article, argued the complex approach to their structures and results under unstable global economic environment. The typology of the free trade zones models and financial linkages types between countries have been developed. Approaches to the results of the free trade zones have been argued. It has been discovered that for the free trade zones of transitional countries the prevailing are tarde flows concentration whereas financial and investment linkages are acting with developed countries. The main directions of increasing of the financial linkages results in the free trade zones have been discovered.